Relasi Makna Dalam Konten Video Pada Akun Instagram Bintang Emon Dan Pemanfaatannya Dalam Pembelajaran Bahasa Indonesia Di SMA - Sabila, Adinda; Juansah, Dase Erwin; Riansi, Erwin Salpa (CV. ULIL ALBAB CORP, 2024)
The video content on the Bintang Emon Instagram account is content that is exclusively uploaded on Instagram social media. Bintang Emon's video content is different from other creators' content, he creates comedy content with the aim of criticizing the government or giving opinions about hot political phenomena. Bintang Emon's Instagram account is currently followed by 6 million users on Instagram. Bintang Emon's content tends to trigger comments from its users, and they often exchange opinions in their uploads. Therefore, the author is interested in researching the meaning relationships in video content on the Bintang Emon Instagram account and its use in learning Indonesian in high school. The method used is a qualitative method with integrated analysis techniques. The approach used is a semantic approach with the hope of being able to interpret the meaning relationships of the words, phrases, clauses and sentences displayed. The results of this research are 6 types of detailed meaning relations, namely: (a) synonymous meaning relations for 3 pieces of data; (b) antonymy meaning relations of 9 data; (c) polysemy meaning relationship of 2 data; (d) ambiguous meaning relationship between 3 pieces of data; (e) hyponymy meaning relationship for 1 piece of data, and; (f) redundancy meaning relationship of 5 pieces of data. The implication in learning Indonesian regarding poetry texts in class 10 (high school level) is that it is hoped that it will make it easier for students to understand and even write poetry texts, where both have the same characteristics, namely that they both use meaning relations in the form of synonymy and homonymy.